2004
DOI: 10.1590/s1413-70542004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito biocida de mandelatos organoestânicos sobre Fusarium oxysporum f. sp. cubense

Abstract: RESUMOCompostos organoestânicos são substâncias que têm sido utilizadas como biocidas. A vantagem do uso dessa classe de compostos é sua degradação em dióxido de estanho (SnO 2 ), que é atóxico para o meio ambiente. Os complexos organoestânicos foram obtidos pela reação de quantidades eqüimolares dos isômeros dos ácidos R-(-)-e S-(+)-mandélicos e de dicloreto de difenilestanho, com o objetivo de testar o efeito biocida dos novos complexos sobre culturas do fungo Fusarium oxysporum f.sp. cubense, avaliando o po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Overall, fungicides have provided unsatisfactory control levels. In vitro , toxicity against Foc has been proved for phosphonate, ambuic acid, organotin mandelates, carbendazim, carboxin, propiconazole, benomyl, and difenoconazole (Davis et al, 1994; Davis and Grant, 1996; Li et al, 2001; Araujo et al, 2004; Somu et al, 2014). In planta , only a few research articles have reported a significant disease control by using fungicides (e.g., carbendazim) (Lakshmanan and Selvaraj, 1984; Eswaramurthy et al, 1988; Roy et al, 1998) or resistance inducers (e.g., indoleacetic acid and menadione sodium bisulphite) (Fernández-Falcón et al, 2003; Borges et al, 2004).…”
Section: Overall Control Strategies Currently Adoptedmentioning
confidence: 99%
“…Overall, fungicides have provided unsatisfactory control levels. In vitro , toxicity against Foc has been proved for phosphonate, ambuic acid, organotin mandelates, carbendazim, carboxin, propiconazole, benomyl, and difenoconazole (Davis et al, 1994; Davis and Grant, 1996; Li et al, 2001; Araujo et al, 2004; Somu et al, 2014). In planta , only a few research articles have reported a significant disease control by using fungicides (e.g., carbendazim) (Lakshmanan and Selvaraj, 1984; Eswaramurthy et al, 1988; Roy et al, 1998) or resistance inducers (e.g., indoleacetic acid and menadione sodium bisulphite) (Fernández-Falcón et al, 2003; Borges et al, 2004).…”
Section: Overall Control Strategies Currently Adoptedmentioning
confidence: 99%
“…1 In the years 1995-2005, we have developed systematic works about the synthesis and characterization of organotin compounds derived from -hydroxycarboxylic acids [2][3][4][5] , which have shown efficient microcide activity on fungi and pathogenic bacteria in agriculture and in humans. [6][7][8] The present investigation relates to the preparation and characterization of a new complex [BuSnLCl2], L = Me2C(OH) COO, characterized by elemental analysis of carbon, hydrogen, chlorine and tin, by infrared, 119m Sn-Mössbauer and 119m Sn-RMN spectroscopies, and the applications of TG and DSC techniques in dynamic helium atmosphere.…”
Section: Introductionmentioning
confidence: 99%